Reflection on feasibility and usability of interactive online international exchange program for occupational therapy students - Natsuka Suyama; Kaoru Inoue; Supatida Sorasak; Chirathip Thawisuk; Masaru Watanabe (Discover Education, 2023)
Abstract The COVID-19 pandemic affected international exchange programs due to travel restrictions. There are few reports of online international exchange programs in medical area and no report of interactive activities among students together for several months. To the best of our knowledge, we needed to seek the feasible approach to conduct online exchange program. We experienced online collaboration works to promote internationalization in occupational therapy (OT) undergraduate education. The aim of this study is to examine the feasibility and usability of an interactive online international exchange program, and discuss its challenges and advantages. The three-month program was newly developed, and aimed at cultivating an international perspective, understanding OT, and learning basic research skills. Students’ interests and the development of their motivation were considered in the program consisting of synchronous and asynchronous lectures, a collaboration research project, group work, and report assignments. Through the program, students were satisfied with the program contents and had the precious experience to develop international relationships. The online exchange program provided students with the opportunity to experience and learn OT education internationally at an economical cost, and to achieve program goal during the regular semester. In this program, students not only acquired knowledge in their professional field, but also cultivated their international communication skills in English from small group activities and social activities. Considering various communication methods was an important aspect in the virtual environment leading to a successful program. In medical education, an online program can be an effective and practical measure for international exchange.